OMNI-CHANNEL BEAUTY ECOSYSTEM AND MUSLIM CONSUMER BEHAVIOR: INSIGHT FROM INDONESIA’S BEAUTY RETAIL MARKET - Fasya, Azizah Nuur; Rahmah, Fitria; Yuliani, Irma (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The beauty retail industry in Indonesia has experienced rapid growth, driven by the increasing adoption of omni-channel strategies that integrate online and offline shopping experiences. Sociolla, as a leading beauty retailer, has pioneered the Omni-Channel Beauty Ecosystem , allowing consumers to seamlessly explore, evaluate, and purchase products across platforms. This study aims to analyze the influence of brand awareness, price, electronic word of mouth (e-WOM), and customer loyalty programs on Muslim consumers’ purchase intention, with a case study at Sociolla Big Mall Samarinda. A quantitative method was employed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with 90 respondents selected according to Hair’s guideline. Data were collected through questionnaires distributed to Muslim consumers who had visited at Sociolla. The findings reveal that brand awareness, e-WOM, and loyalty programs have a significant positive effect on purchase intention, while price does not show a significant influence. These results highlight the importance of brand equity, digital engagement, and loyalty strategies over pricing in shaping consumer decisions within a non-metropolitan omni-channel beauty ecosystem.